Removal of congo red azo dye from aqueous solution by ZnO nanoparticles loaded on multiwall carbon nanotubes - Seyed Arabi, Seyed Masoud; Lalehloo, Rahman Shakibaei; Olyai, Mohamad Reza Talei Bavil; Ali, Gomaa A. M.; Sadegh, Hamidreza (Elsevier, 2019)
The present work investigates the performance of ZnO nanoparticles loaded on multiwall carbon nanotubes for removing of congo red dye from aqueous solutions. The prepared nanocomposites are characterized by XRD, TEM, FTIR, FESEM and EDX. The effect of various parameters such as contact time, temperature and adsorbent dosage are investigated and discussed. The obtained results show that the optimum adsorption conditions are contact time of 50 min., 55 °C and dosage of 9 mg. These optimum parameters give a high removal ratio of 99.8%.The adsorption data were well fitted by pseudo-second-order model. The obtained results reveal that ZnO/MWCNTs is a promising, environmentally friendly and efficient adsorbent for some wastewater treatment.